Evaluation of respiratory function at 6 years of age in patients with cystic fibrosis with frequent pulmonary exacerbations in the first 2 years of life - Tabakci, Sati Ozkan; Cinel, Guzin; Uytun, Salih; Polat, Sanem Eryilmaz; Yalcin, Ebru; Kiper, Nural; Ersoz, Deniz Dogru (European Respiratory Soc Journals Ltd, 2023)
[Abstract Not Available]
Annual Congress of the European-Respiratory-Society (ERS) -- SEP 09-13, 2023 -- Milan, IA